Elephants and savanna woodland ecosystems : a study from Chobe National Park, Botswana - Skarpe, Christina, 1946-; Du Toit, Johan T.; Moe, Stein R., 1960- (Conservation science and practice series ;, 2014)
BLURB TO COME! DO NOT USE TEXT BELOW! The proposed book will be composed of 16 chapters, each written by one lead author and 2-7 additional authors/contributors. The book draws on the results of five years research on the dynamics of an ecosystem where elephant and antelope populations were severely decimated more than a century ago, and then recovered. We show that both the decline and return of elephants caused profound ecosystem perturbations. A heterogeneity framework (Pickett et al. 2003) provides the conceptual structure of the book. Following Pickett et al. (2003) we consider the e.